Equity in healthcare financing in Nigeria (2016)
Using both graphical and geometric analyses, this paper examines the extent of inequity in healthcare finance among the Nigerian population. One of the acclaimed plans in healthcare in this teeming community is the mix method of financing but the system in practise is dominated with Out-of-Pockets (OOPs) meanwhile the degree of income inequality still remain high. Using the Nigerian Living Standard Survey (NLSS) data conducted in 2004, the framework for this study relies on Kakwani Progressivity Index (KPI). A decomposition of the groups into lower and upper bound however, reveal that health payment for lower bound is regressive while payment for upper bound is progressive. Although, the upper bound result dominates the entire result which finally suggests a progressive system arising from the spending habit of the rich in seeking for healthcare services abroad.